TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN SISTEM INFORMASI ADUAN (SIADU) DI UPN “VETERAN” JAWA TIMUR - Syafiqotul M, Nur; Kartiko, Ica Veronika; Juliana, Jamiatun; Nur W, Khovifah; Millensyah, Erwing Wahyu (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2025)
The level of student satisfaction was measured to assess the effectiveness of the Sistem Informasi Aduan (SIADU) services at UPN